>
#mathematics
,
#functions
,
#in-mathematic-grade-11
>
Let f(x)=3x-4 &g(x)=x^2+3x,then (fog)(-1) is equal to
A)10
B)-10
C)28
D-28
?

Oct 29, 2023

Sort By

ChatGPT

Oct 29, 2023

To find (fog)(-1), we need to substitute -1 into g(x) first and then substitute the result into f(x).

Substituting -1 into g(x), we get:

g(-1) = (-1)^2 + 3(-1) = 1 - 3 = -2

Now, substituting -2 into f(x), we get:

f(-2) = 3(-2) - 4 = -6 - 4 = -10

Therefore, (fog)(-1) = -10.

The correct answer is B) -10.

Substituting -1 into g(x), we get:

g(-1) = (-1)^2 + 3(-1) = 1 - 3 = -2

Now, substituting -2 into f(x), we get:

f(-2) = 3(-2) - 4 = -6 - 4 = -10

Therefore, (fog)(-1) = -10.

The correct answer is B) -10.

Ask an expert